Understanding of Severe Sepsis and Septic Shock Among Emergency Department and Intensive Care Unit Medical Officers in a Developing Country Nepal: A Survey Study - Shrestha, G.S.; Parajuli, B.P.; Acharya, S.P.; Banstola, A.; Upadhyay, B.; Bajracharya, T. (Birat Journal of Health Sciences, 2017)
Introduction Severe sepsis and septic shock is a major cause of morbidity and mortality. The burden is higher and the outcome is dismal in the low and middle income countries.Objective This study aims to evaluate the knowledge about severe sepsis and septic shock among the medical officers of emergency department and intensive care unit in Nepal. It is a cross-sectional survey study.Methodology The medical officers working in emergency department and intensive care unit were asked to fill up the survey questionnaire, which contained the questions related to the demographics of the participant, about the knowledge of sepsis and the hindrances behind the effective management of septic patients. The percentage of correct answers for each question and average correct response for all the questions were analyzed.Results Seventy medical officers from twenty-four hospitals across the country were enrolled in the study. Among them, 39 were working in the emergency department and 31 were working in the intensive care unit. For the individual questions, the percentage of correct answers varied from 8.57% to 82.86% (average 48.16%). As per the response of the participants, lack of knowledge about sepsis and management guidelines, lack of experience for management of sepsis and lack of investigation facilities were considered to be the major barriers for effective management of septic patients.Conclusions Knowledge and understanding about severe sepsis and septic shock among the medical officers of emergency department and intensive care unit in Nepal is sub-optimal. To improve the outcome of septic patients, efforts should be made to increase the understanding among these first-line health care workers by implementing regular and mandatory training programs.Birat Journal of Health Sciences 2016 1(1): 47-50